2017
DOI: 10.1002/ejlt.201700335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Temperature and Duration on Bioactive Concentrations in the Seed and Oil of Brassica napus (Canola)

Abstract: The effects of storage temperature and duration on phytosterol, tocopherol and carotenoid concentrations are assessed in canola seed, and oil extracted using two different techniques, over a 10 month period. Increases to oxidation indices (K232, K270 and ΔK) are observed in the solvent extracted oils, and in the seed stored at 40 °C, indicating the formation of primary and secondary oxidation products. Only small decreases in the concentrations of γ‐tocopherol and β‐carotene are observed across the 10 month pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In our earlier studies, we showed that adverse storage conditions (10-15% moisture content and temperature of 25-30°C) produce a statistically significant reduction in the level of lipophilic compounds such as tocochromanols and phytosterols (Gawrysiak-Witulska et al, 2012;. Flakelar et al (2018) also observed losses of phytosterols; however, they showed no statistically significant changes in the levels of individual phytosterols or their total contents in the function of temperature. They also showed that phytosterol losses were similar, irrespective of the fact whether their content was analysed in the samples stored as seeds or Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In our earlier studies, we showed that adverse storage conditions (10-15% moisture content and temperature of 25-30°C) produce a statistically significant reduction in the level of lipophilic compounds such as tocochromanols and phytosterols (Gawrysiak-Witulska et al, 2012;. Flakelar et al (2018) also observed losses of phytosterols; however, they showed no statistically significant changes in the levels of individual phytosterols or their total contents in the function of temperature. They also showed that phytosterol losses were similar, irrespective of the fact whether their content was analysed in the samples stored as seeds or Fig.…”
Section: Resultsmentioning
confidence: 83%
“…In turn, seeds with a moisture content of 9-10% may be stored for 3 months (Salunkhe et al, 1992). Results reported by Flakelar et al (2018) indicate that the accumulation of free fatty acids will remain within the admissible limits for 10 months on condition the seed moisture content, oil exposure to light and exposure to extreme temperatures are limited to the minimum. According to Matthäus (2013), seeds with a 7% moisture content are stable during 9-month storage.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our earlier studies, we showed that adverse storage conditions (10-15% moisture content and temperature of 25-30°C) produce a statistically significant reduction in the level of lipophilic compounds such as tocochromanols and phytosterols (Gawrysiak-Witulska et al, 2012;. Flakelar et al (2018) also observed losses of phytosterols; however, they showed no statistically significant changes in the levels of individual phytosterols or their total contents in the function of temperature. They also showed that phytosterol losses were similar, irrespective of the fact whether their content was analysed in the samples stored as seeds or oil.…”
Section: Resultsmentioning
confidence: 83%
“…In fact, linoleic acids are usually used as indicators of the extent of fat deterioration because it is more susceptible to oxidation than saturated fatty acids. Therefore, the C18:2/C16:0 ratio is also used to indicate the degree of oxidative deterioration in frying oil (Flakelar et al ) . Overall, our results indicate that the oxidation resistance was higher in HCR than in LCR.…”
Section: Resultsmentioning
confidence: 99%